Deciphering the Role of Shugoshin-Like Protein 1 in Lung Adenocarcinoma: A Comprehensive Analysis and In Vitro Study - Yuan, Yixiao; Wang, Juan; Zhang, Dahang; Tang, Lin; Duan, Lincan; Jiang, Xiulin (Frontiers in Oncology, 2022)
Lung adenocarcinoma (LUAD) remains the most common deadly disease and has a poor prognosis. Shugoshin-like protein 1 (SGO1) has been characterized in its function in correct cell division and its role in centrosome cohesion in the nucleus. However, the underlying biological function and potential mechanisms of SGO1 driving the progression of lung adenocarcinoma remains unclear. In this study, we found that SGO1 was increase in LUAD tissues and cell lines. Upregulation of SGO1 expression was correlates with poor overall survival (OS), disease-free survival (DSS), and progression-free survival (PFS) in patients with LUAD. ROC curve analysis showed that the AUC value of SGO1 was 0.983. Correlation analysis showed that SGO1 expression was associated with immune infiltration in LUAD. Meanwhile, a potential ceRNA network was constructed to identify lncRNA-MIR4435-2HG /miR-125a-5p/ SGO1 regulatory axis in LUAD. Finally, we determine that SGO1 regulated cell proliferation and cell apoptosis of lung adenocarcinoma in vitro. In conclusion, our data suggested that SGO1 could be a novel prognostic biomarker for lung adenocarcinoma.